Pendampingan Pembelajaran Metode Qiro'ati Bagi Anak-Anak Pondok Alif Lam Mim - Teguh Handoyo,; Ana Chonitsa,; Adinda Riski Amalia,; Siti Salamah,; Inayah Priyatun,; Ayu Febrianti,; Elsa Tiara,; Rifani Raniasati,; M. Maskur Musa,; Amma Chorida Adila,; Hendri Hermawan Adinugraha, (Joong-Ki : Jurnal Pengabdian Masyarakat, 2022)
Learning to read the Qur'an has the meaning of an effort made by the ustadz or cleric to his students to understand the procedures for reading the Qur'an as a whole with correct and precise readings. Community service activities through mentoring learning the qiro'ati method for children at the Alif Lam Mim Islamic boarding school aim to ensure that the teaching carried out can run well in accordance with Islamic religious guidance as desired by Allah SWT and Rasulullah SAW through His revelations and treatises. The research that has been carried out aims to determine the process of Qiro'ati Method Learning Assistance for the Children of Pondok Alif Lam Mim. The approach used in this community service activity includes the qiro'ati method, lectures, and questions and answers. The results of this study indicate that community service activities carried out with qiro'ati learning mentoring for Alif Lam Mim Islamic boarding school children are as follows: first, adding insight and knowledge to students about the science of recitation and the qiro'ati method. Second, fostering the spirit of students in improving the science of recitation, and third helping educators in implementing the qiro'ati method in learning to read the Qur'an at the Alif Lam Mim Islamic Boarding School.